Company Culture As An Alternative Solution To Prevent Fraud In Workplace - prasetyo, handoyo (Veteran Law Review, 2019)
The company is one of the supporting factors for national economic and development, contributors to foreign exchange and taxes to the state and provides jobs and workplaces needed by many people to fulfill their daily needs, so that their presence in daily life cannot be ignored and has become a necessity which is non-negotiable. Along with the development of the corporation which is increasing its operational activities, opportunities arise to conduct unethical behavior carried out by some employees to obtain additional benefits illegally by utilizing their position and experience in the workplace (called The Trust Violator Officer). Many attempts were made to prevent and overcome fraudulent behavior, but the authors offer one more solution to prevent behavior fraud in the workplace, which focuses more on the root problem of the emergence of fraud behavior, namely by fixing the character of new employees by early instilling the company's noble culture that contains universal good norms, in which a commitment is also made to take actions based on business ethics and work ethics. With the development of this anti-fraud commitment early on when new employees are accepted and start work, it is hoped that it will cut the fraud learning chain which traditionally flows from senior to junior fraudsters.